HEGEMONI AMERIKA SERIKAT DI SERI KOMIK CAPTAIN AMERICA STEVE ROGERS - Rafiqoh Fitriani; Hanny Hafiar; Ari Agung Prastowo (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
This research aimed to describe a critical discourse analysis about hegemony where United States positionedtheir country as superpower country in Captain America: Steve Rogers comic series. Method used in thisresearch was Critical Discourse Analysis Norman Fairclough with qualitative data and critical paradigm. Theresults of this research showed that Captain America: Steve Rogers comic series has hegemony messages ofUnited States as superpower country. It was reflected through appearance, personality, words, and theideology of Captain America while positioning the enemy as the opposites of the aspects above. CaptainAmerica: Steve Rogers used social, historical, and political factors to ease their hegemony messages beingabsorbed by reader. The conclusion of this study is Captain America: Steve Rogers comic series have nationbranding hegemony messages of the United States as a superpower country. Furthermore, it is expected thatthe study about hegemony would get more attention because hegemony subject would evolve socially andideologically in our society.